2014
DOI: 10.1089/jpm.2013.0684
|View full text |Cite
|
Sign up to set email alerts
|

End-of-Life Care Planning: Improving Documentation of Advance Directives in the Outpatient Clinic Using Electronic Medical Records

Abstract: EMR-based reminders are effective in improving documentation rates of ADs. Further research is needed to establish whether improved documentation impacts inpatient management and costs of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 35 publications
0
49
0
Order By: Relevance
“…would lead with focused guiding questions (see Supplemental Appendix A) that allowed discussion to follow in a flexible way but without losing sight of the purpose of the study, following Witzel's concepts of problem-centred interviews. 27 The interviews were designed to be semi-structured, but within this frame and depending on the timing of the interview, they could be used in two different ways, following postpositivism and constructivism:…”
Section: Study Methodsmentioning
confidence: 99%
“…would lead with focused guiding questions (see Supplemental Appendix A) that allowed discussion to follow in a flexible way but without losing sight of the purpose of the study, following Witzel's concepts of problem-centred interviews. 27 The interviews were designed to be semi-structured, but within this frame and depending on the timing of the interview, they could be used in two different ways, following postpositivism and constructivism:…”
Section: Study Methodsmentioning
confidence: 99%
“…With the advent of the Electronic Medical Record (EMR), the stage was set for new opportunities to allow for reminder systems as well as regimentation of documentation to facilitate requests for an execution of advance directives. One intervention used a reminder system within the EMR to set parameters of chronic illness that ultimately assisted in improved documentation rates of advance directives by over six-fold [6]. On the other hand, another study showed that the EMR can ultimately result in multiple, duplicative locations for advance directive documents, and that standardization for advance care planning documentation is necessary [7].…”
Section: Introductionmentioning
confidence: 99%
“…8 A pilot quality improvement program directed toward internal medicine residents and their elderly patients showed that improvement in AD completion rates was tied to adding ADs to patients' active problem lists and giving PCPs easy access to electronic health record documentation. 1 Jezewski et al 12 examined 25 studies, 14 of which were directed to participants who were age 50 or older. The studies were categorized by the approaches, didactic or interactive, used to improve completion rates of ADs.…”
Section: Summary Of the Evidencementioning
confidence: 99%